Sahida - Assouline, Natalie (Israel : Kleinhendler, Talia ; Ephrati, Ayelet, 2008)
A poignant chronicle of the lives of women serving time in prison for involvement in terrorist attacks in Israel. Filmed over the course of two years, the film strives to uncover the motivations behind the actions of these women. We share their daily prison lives, giving birth, meeting families, attending classes, and gossiping about clothes. One woman coyly describes wanting to blow up a hospital which treated her for severe burns following a kitchen accident, even though the Israeli doctors were kind. Another cuddles her son and says she wanted to destroy an Israeli kindergarten. Yet another, a mother of five, is serving three life terms for transporting male suicide bomber, who is told killed pregnant women but shows no signs of retraction. We hear of religious ideology, but also of discrimination and despair in the world these women come from. A journey into the world where the greatest cruelty lurks beneath the most striking beauty, where a lullaby whispered lovingly in a baby's ear echoes with the sting of hatred, and where compassion and cold blooded disdain live together behind the same penetrating eyes. A moving film full of contradictions.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films